Implementation of Human Resource Management Strategy in Improving Organizational Performance - Pertiwi, Triani (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This study aims to investigate the implementation of the integration process of the company's strategic plan and HRD strategic plan to enhance the competitive advantage of PT CSI. The data collection was through in-depth interviews, secondary data, and primary data from HRD in 2019. Qualitative research methods, with a case study approach were utilized for this investigation. The study's findings suggest a lack of orientation towards comprehensive investment in the implementation of Human Resource Management. Despite an integration and adaptation of the process to increase competitive advantage, HRD is still viewed as a cost center. HRD companies have participated in the planning process. The everyday practice of Human Resource Management does not seem to fully depict its alignment with organizational strategy. The results reveal that HRD maintains a dual relationship with policy makers, wherein issues and implications encountered in HR management are considered during the formulation of the strategic plan.